Leadership Management to Enhance Supervisor Performance in Educational Institutions - Muhammad Arsad; Maisah Maisah; Fadlilah Fadlilah (PT. Riset Press International, 2025)
This study aims to analyze the leadership and management practices of the Heads of the Ministry of Religious Affairs Offices in improving the performance of supervisors at State Islamic Senior High Schools in Jambi Province. Utilizing a qualitative approach with a phenomenological method, the research was conducted across several local Ministry offices. The findings reveal four key aspects. First, performance improvement planning is typically conducted through coordination meetings at the beginning of the academic year. Second, supervisor performance enhancement is carried out through official briefings, routine school visits, and both formal and informal coaching, though its implementation remains inconsistent due to limited time, the advanced age of many supervisors, and the broad scope of their responsibilities. Third, performance monitoring tends to emphasize administrative compliance rather than substantive areas such as managerial guidance or support for the Merdeka Curriculum. Fourth, key obstacles include a shortage of qualified supervisors, insufficient training provided by the Ministry, and weak structural alignment between Ministry leadership and supervisor working groups, which often operate independently. The study recommends the strengthening of technical regulations, recruitment of subject-specific supervisors, implementation of continuous curriculum-based training, and the empowerment of Ministry heads as strategic leaders in supervisory management. Strengthening these aspects is expected to significantly enhance the quality of madrasah education in the region.